Foreign Language Learning Curriculum Management at the Zainul Hasanain Genggong Pajarakan Islamic Boarding School - Lailatul Fitria; Abd. Aziz Wahab; Poppy Rachman (Maharot : Journal of Islamic Education, 2023)
The purpose of this research is to describe the management of the foreign language learning curriculum at the Zainul Hasanain Genggong Pajarakan Islamic Boarding School. This research method uses qualitative-descriptive. Data collection techniques through observation and interviews. Data analysis was carried out from data collection, data reduction, data presentation, and drawing conclusions. Meanwhile, source triangulation is used as a data validation technique. The results of this study explain that the management system for foreign language learning curriculum at Zainul Hasanain Islamic Boarding School is quite good and well organized. It is known that the curriculum management applied is the same as the stages of management in general (planning, actuating, and evaluating). The planning process formulated objectives, program of activities, and schedule of activities. Then the implementation is carried out by implementing continuous activities such as memorizing vocab/mufrodat, grammar/qowaid nahwu-shorrof, short activities, and muthola'ah. There is also an annual program held to see the success and skill level of learning foreign languages such as story telling or qisshoh, and to undergo assignments for two years. Finally, evaluation of student learning is carried out once every three months.